Pengaruh Biaya Bahan Baku, Biaya Tenaga Kerja Langsung, dan Biaya Overhead Pabrik terhadap Laba Bersih pada PT Duta Persada Teknik - Alvian Nur Khakim; Cahyadi Husadha; Elia Rossa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this research is to test and analyze the effect of raw material costs, direct labor costs, and factory overhead costs on net profit. This research method uses quantitative research methods by paying attention to the type and source of data, namely secondary data obtained from corporate securities reports. The research population and sample are the financial reports of PT. Persada Engineering Ambassador from 2016 to 2022. The analytical methods used are descriptive statistical tests, classical hypothesis tests, multiple linear analysis tests, and hypothesis tests. The results of this research show that raw material costs have a significant effect on net profit, direct labor costs have a significant effect on net profit, and factory overhead costs have a significant effect on net profit.